Astragalus Polysaccharide RAP Selectively Attenuates Paclitaxel-Induced Cytotoxicity Toward RAW 264.7 Cells by Reversing Cell Cycle Arrest and Apoptosis - Bao, Wan-Rong; Li, Zhi-Peng; Zhang, Quan-Wei; Li, Li-Feng; Liu, Hong-Bing; Ma, Dik-Lung; Leung, Chung-Hang; Lu, Ai-Ping; Bian, Zhao-Xiang; Han, Quan-Bin (Frontiers in Pharmacology, 2019)
Purpose: The purpose of this study was to determine if an Astragalus polysaccharide (RAP) can protect immune cells from the toxic side effects of paclitaxel (Taxol), a powerful anti-tumor drug whose equally powerful side effects limit its clinical use. Methods: We hypothesized that RAP can reduce the toxic effects induced by Taxol. To test this hypothesis, we conducted a series of studies in vivo and in vitro. First, we confirmed RAP’s effects in vivo utilizing BALB/c mice inoculated with 4T1 mouse breast cancer cells as the tumor model. Mice were treated with RAP and/or Taxol, and the differences in the life spans were recorded. Second, a co-culture cell model was used to study the protective effect of RAP on cells vis-a-vis Taxol. The cell cycle and apoptosis of RAW 264.7 cells that were treated with RAP with/without Taxol were checked by flow cytometry and Hoechst staining. Proteins involved in the cell cycle and apoptosis were also tested by Western blot to reveal the probable mechanism. Results: RAP prolonged the life span of tumor-bearing mice treated with Taxol. The in vitro experiments showed that Taxol suppressed the proliferation of RAW 264.7 cells while RAP protected the RAW 264.7 cells from Taxol-induced suppression. The protection is selective because RAP had no effect on 4T1 cells. Furthermore, Taxol clearly led to cell cycle arrest mainly at the G2/M phase and generated cytotoxicity against RAW 264.7 cells, while RAP blocked cell cycle arrest and protected cells from apoptosis. Taxol up-regulated the protein levels of P-H2A, PARP, Chk1, p53, and p21 and down-regulated Bcl-Xl and Mcl-1, and RAP reversed the expression of all these proteins. Conclusion: These results suggested that RAP can protect immune cells from Taxol-induced toxicity, by changing the cell cycle and apoptosis.